Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/01635581.2016.1180407
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Oleocanthal Isolated from Virgin Olive Oil on Human Melanoma Cells

Abstract: Oleocanthal is one of the phenolic compounds of extra virgin olive oil with important anti-inflammatory properties. Although its potential anticancer activity has been reported, only limited evidence has been provided in cutaneous malignant melanoma. The present study is aimed at investigating the selective in vitro antiproliferative activity of oleocanthal against human malignant melanoma cells. Since oleocanthal is not commercially available, it was obtained as a pure standard by direct extraction and purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 20 publications
1
77
1
1
Order By: Relevance
“…In this regard, (−)-oleocanthal can be an appealing option to improve sensitivity to endocrine treatments in luminal breast cancer and reduce the emergence of resistance to hormonal therapies. This is particularly interesting taking into consideration that the antiproliferative effects of (−)-oleocanthal in cancer cell lines are achieved at concentrations that have no or little effect on the viability of non-tumorigenic cells and its exceptionally potent in vivo activities as indicated by multiple previous studies (Akl et al, 2014; Fogli et al, 2016; Pei et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, (−)-oleocanthal can be an appealing option to improve sensitivity to endocrine treatments in luminal breast cancer and reduce the emergence of resistance to hormonal therapies. This is particularly interesting taking into consideration that the antiproliferative effects of (−)-oleocanthal in cancer cell lines are achieved at concentrations that have no or little effect on the viability of non-tumorigenic cells and its exceptionally potent in vivo activities as indicated by multiple previous studies (Akl et al, 2014; Fogli et al, 2016; Pei et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that (−)-oleocanthal is a potential inhibitor of the hepatocyte growth factor receptor (c-Met) pathway in breast cancer cells (Akl et al, 2014; Elnagar et al, 2011; Mohyeldin et al, 2016b). The antiproliferative effects of (−)-oleocanthal are mediated by inhibiting multiple c-Met downstream signaling molecules including protein kinase B (Akt), mitogen-activated protein kinase (MAPK), signal transducers and activators of transcription-3 (STAT-3), and mammalian target of rapamycin (mTOR) in multiple cancer cells (Akl et al, 2014; Fogli et al, 2016; Khanal et al, 2011; Khanfar et al, 2015; Pei et al, 2016; Scotece et al, 2013). In addition, (−)-oleocanthal induced cancer cell arrest by modulating the expression of cyclins, cyclin-dependent kinases, and arrest proteins (Akl et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several groups have demonstrated oleocanthal’s ability to inhibit key proteins that promote cell growth and survival (12, 14-17, 40), a unifying mechanism for the specific and irreversible cellular death-inducing properties of oleocanthal has not been established. In this report, we observed that a transient exposure of cancer cells to oleocanthal for one hour resulted in the loss of cell viability after 24 hours.…”
Section: Discussionmentioning
confidence: 99%